"With you, with me, with everyone". Our plan for coexistence. (Journal of Parents and Teachers, 2012)
In this article explained the CEIP Coexistence Plan. “Maria Sanz de Sautola” offers an analysis of the context and main parts of this Plan and its implementation in primary education. This school wants to make emotional education a key capacity  in the learning process, always understanding it as a capacity that the student learns and that tries to increase the personal and social welfare of the student.
Keywords: Coexistence plan; emotional education; experiences; primary education.